Estimation Of Water Saturation In Carbonate Reservoirs Without Resistivity Log Data. Part Ii: Formulation Of A New Model - Bambang Widarsono; Heru Atmoko; Ridwan Ridwan; Kosasih Kosasih (Testing Center for Oil and Gas LEMIGAS, 2009)
This paper is the second part of the two-part report on study for establishing alternative models that are valid for Indonesian carbonate reservoirs. In this second part formulation of the new models is presented. For the study, 407 plug samples taken from various limestone reservoirs in Indonesia were used. Following Lucia’s procedure the samples were classified, grouped, averaged, and their capillary pressure data was formulated to form water saturation models that are essentially functions of porosity and height above free water level. Validity test on the models are performed on two wells in West Java with very encouraging results. With using the Archie model as reference, justified using well test data, the new models prove themselves reliable while the original Lucia models provide far too optimistic estimates. The model validity check shows tha the models are valid for at least Class 1 and Class 2 rocks in accordance with Lucia classification. Study on Class 3 rock is needed in the future